Comparative cost-effectiveness of focal and total salvage 125I brachytherapy for recurrent prostate cancer after primary radiotherapy - Peters, Max; Piena, Marjanne A.; Steuten, Lotte M.G.; Zyp, Jochem R.N. van der Voort van; Moerland, Marinus A.; Vulpen, Marco van (Journal of Contemporary Brachytherapy, 2016)
Purpose: Focal salvage (FS) iodine 125 ( 125 I) brachytherapy could be an effective treatment for locally radiorecurrent prostate cancer (PCa). Toxicity is often reduced compared to total salvage (TS) while cancer control can be maintained, which could increase cost-effectiveness. The current study estimates the incremental cost per quality-adjusted life year (QALY) of FS compared to TS. Material and methods: A decision analytic Markov model was developed, which compares costs and QALYs associated with FS and TS. A 3-year time horizon was adopted with six month cycles, with a hospital perspective on costs. Probabilities for genitourinary (GU) and gastrointestinal (GI) toxicity and their impact on health-related quality of life (SF-36) were derived from clinical studies in the University Medical Center Utrecht (UMCU). Probabilistic sensitivity analysis, using 10,000 Monte Carlo simulations, was performed to quantify the joint decision uncertainty up to the recommended maximum willingness-to-pay threshold of €80,000/QALY. Results: Focal salvage dominates TS as it results in less severe toxicity and lower treatment costs. Decision uncertainty is small, with a 97-100% probability for FS to be cost-effective compared to TS (€0-€80,000/QALY). Half of the difference in costs between FS and TS was explained by higher treatment costs of TS, the other half by higher incidence of severe toxicity. One-way sensitivity analyses show that model outcomes are most sensitive to utilities and probabilities for severe toxicity. Conclusions : Focal salvage 125 I brachytherapy dominates TS, as it has lower treatment costs and leads to less toxicity in our center. Larger comparative studies with longer follow-up are necessary to assess the exact influence on (biochemical disease free) survival and toxicity.